Pengembangan Budaya Organisasi di Lembaga Peradilan - GAFFAR, JANEDJRI M. (UI Scholars Hub, 2010)
This research concerns with organizational culture in a judiciary institution, with a case study at the Secretariat General and Clerk’s Office of the Indonesian Constitutional Court. The purpose of this research is to learn about the organizational culture growing in the institution, identify the appropriate culture and formulate choices of possible development. This research used qualitative approach. The data were collected through the method of observation, survey, and focus group discussion. The result of this research shows that in the dimension of external adaptation tasks, the culture developed in the Secretariat General and Clerk’s Office of the Indonesian Constitutional Court are the modern, rational, immediate, precise, and result-oriented culture. The development of organizational culture in the Secretariat General and Clerk’s Office of the Indonesian Constitutional Court is oriented to the shaping of impartial, integrated, immediate, precise, and professional culture.